2011
DOI: 10.4049/jimmunol.1001963
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ Cells Enhance Resistance to Pulmonary Serotype 3 Streptococcus pneumoniae Infection in Mice

Abstract: Despite the success of the pneumococcal conjugate vaccine, pneumococcal pneumonia remains a significant clinical problem, and there is still much to learn about natural resistance and cellular immunity to pneumococcus. We investigated the role of T lymphocytes in resistance to serotype (ST) 3 Streptococcus pneumoniae in an intranasal infection model in C57BL/6 (wild-type [Wt]) and CD8+ (CD8−/−)- and CD4+ (MHC class II−/−)-deficient mice. CD8−/− mice exhibited significantly more bacterial dissemination and lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 51 publications
3
77
0
Order By: Relevance
“…Furthermore, in the absence of IFN-g, decreased levels of chemokines involved in neutrophil recruitment, as well as neutrophils themselves, were reported by some groups (23,26), and this was associated with a lower bacterial load (23). More recently, and in contrast, IFN-g-deficient mice were argued to have higher levels of neutrophils and chemokines associated with their recruitment, as well as increased bacterial load (25). Alternatively, IFN-g may influence pneumococcal clearance via modulation of macrophage scavenger receptors.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in the absence of IFN-g, decreased levels of chemokines involved in neutrophil recruitment, as well as neutrophils themselves, were reported by some groups (23,26), and this was associated with a lower bacterial load (23). More recently, and in contrast, IFN-g-deficient mice were argued to have higher levels of neutrophils and chemokines associated with their recruitment, as well as increased bacterial load (25). Alternatively, IFN-g may influence pneumococcal clearance via modulation of macrophage scavenger receptors.…”
mentioning
confidence: 99%
“…More recently, it was shown that S. pneumoniae may also be recognized by inflammasomes that are dependent upon the adaptor molecule ASC (16)(17)(18)(19). Together, these pathways initiate immune activation and lead to production of inflammatory cytokines and chemokines that subsequently mediate the recruitment of leukocytes to the site of infection (20)(21)(22)(23)(24)(25)(26). However, when this occurs within the brain, the ensuing inflammatory response is argued to ultimately cause neuronal damage and/ or death (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…+ T cell responses play important roles in clearance of S. pneumoniae, contributing to the anti-microbial host response through activation of phagocyte-driven microbial killing, while CD8 + T cells may have important roles regulating the extent of Th17 responses and neutrophilic inflammation [40][41][42][43]. Although adaptive immune responses contribute to these responses, innate immunity can amplify responses in the form of monocyteinduced stimulation of memory T cells, and innate responses generated by cells such as invariant natural killer T cells (iNKT) can prime phagocyte bacterial killing [41,[43][44][45].…”
Section: Alveolar Macrophages Role In Host Defence Against Pulmonary mentioning
confidence: 99%
“…The capacity of IL-10 to modulate the host inflammatory immune response together with the fact that lung inflammation during S. pneumoniae infection is associated with increased bacterial dissemination and severe disease, [23][24][25] would suggest that IL-10 is required to prevent bacterial dissemination during S. pneumoniae infection. Here we show that S. pneumoniae (strain D39) leads to a significant increase in the expression of IL-10 in the lungs of infected mice.…”
Section: Introductionmentioning
confidence: 99%